Characterization of glycerophospholipids at multiple isomer levels via Mn(ii)-catalyzed epoxidation. Issue 21 (21st September 2022) - Chen, Xi; Tang, Shuli; Freitas, Dallas; Hirtzel, Erin; Cheng, Heyong; Yan, Xin
Abstract : A novel and bifunctional derivatization method utilizing Mn(ii )-catalyzed epoxidation simultaneously identifies lipid CC bond- and sn-positional isomers. Abstract : Characterization of glycerophospholipid isomers is of significant importance as they play different roles in physiological and pathological processes. In this work, we present a novel and bifunctional derivatization method utilizing Mn(ii )-catalyzed epoxidation to simultaneously identify carbon–carbon double bond (CC bond)- and stereonumbering ( sn )-positional isomers of phosphatidylcholine. Mn(ii ) coordinates with picolinic acid and catalyzes epoxidation of unsaturated lipids by peracetic acid. Collision-induced dissociation (CID) of the epoxides generates diagnostic ions that can be used to locate CC bond positions. Meanwhile, CID of Mn(ii ) ion-lipid complexes produces characteristic ions for determination of sn positions. This bifunctional derivatization takes place in seconds, and the diagnostic ions produced in CID are clear and easy to interpret. Moreover, relative quantification of CC bond-and sn -positional isomers was achieved. The capability of this method in identifying lipids at multiple isomer levels was shown using lipid standards and lipid extracts from complex biological samples.